دراسة استكشافية لواقع الاستثمار الأجنبي المباشر في سورية - الحسين محمد; اليوسف جمال; صقر منال (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث الحالي واقع الاستثمار الأجنبي المباشر في سورية من خلال تعرف مشاريع الاستثمار الأجنبي المباشر المشملة خلال الفترة 1991-2010 في سورية, وعدد فرص العمل الناتجة عن هذه المشاريع, وتوزع هذه المشاريع على المحافظات السورية. وتكمن أهمية البحث في دور الاستثمار الأجنبي المباشر في تغطية العجز التمويلي للدولة المضيفة بالمقارنة مع التدفقات الأخرى لرأس المال, وسد فجوة الموارد المحلية المالية والبشرية, وتسريع الاندماج في النظام العالمي الذي من الممكن أن يسهم في زيادة معدل النمو الاستثماري وكبح معدل البطالة. وبينت نتائج البحث أهمية الاستثمار الأجنبي المباشر وأبعاده في التنمية الاقتصادية والاجتماعية, إذ إن جذب الاستثمارات وعلى الأخص الاستثمار الأجنبي المباشر يرتبط بإيجاد بيئة استثمارية مناسبة, الأمر الذي يستدعي توفير المناخ الاقتصادي والسياسي المناسبين لجذب الاستثمار الأجنبي المباشر فضلاً عن اتخاذ التدابير الممكنة كلها لرسم سياسة استثمارية مواتية واستخدام طرق الترويج الاستثماري بهدف تحسين مستوى الاستثمار ليشمل القطاعات الاقتصادية المختلفة ويغطي جميع المحافظات. The present research deals with the reality of foreign direct investment in Syria through the recognition of foreign direct investment projects during the period 1991-2010 in Syria, and the number of jobs resulting from these projects as well as the distribution of these projects on the provinces of Syria. The importance of research comes from the fact that foreign direct investment covers the funding gap of the host country compared with other flows of capital, filling the resource gap of local financial and human resources, and accelerating integration into the global system, which could contribute in increasing the rate of investment growth and curb unemployment The results of research assures the importance of foreign direct investment and its dimensions in the economic and social development, as the attraction of investment, - particularly foreign direct investment - related to creating an environment appropriate investment – something which requires the provision of economic and political environment suitable for attracting foreign direct investment as well as taking possible measures are to draw a policy favorable investment and the use of methods of investment promotion in order to improve the level of investment to include the various economic sectors and covers all the provinces.